Salidroside protects against myocardial infarction via activating MIF-mediated mitochondrial quality control - Baiyang You; Jie Zhang; Chuyan Yang; Yaoshan Dun; Dake Qi; Yuqiong Long; Jing Cheng; Yuan Lin; Nanjiang Zhou; Tanghao Zeng; Jie Dong; Suixin Liu (Chinese Medicine)
Abstract Background Salidroside is a potential therapeutic agent for myocardial infarction (MI), exerting therapeutic effects on macrophage migration inhibitory factor (MIF)-regulated mitochondrial quality control. Our aim was to explore the mechanism through which the MIF pathway regulates salidroside-mediated resistance to hypoxia-induced cardiomyocyte apoptosis. Methods Ligation surgery of the left anterior descending branch of the coronary artery was employed to establish a myocardial infarction mouse model. Salidroside at low and high doses was administered to the mice for 4 weeks after the surgery. Cardiac function was evaluated via echocardiography. Morphological changes, apoptosis, and mitochondrial damage in the myocardium were examined. For the cell experiments, cardiomyocytes were treated with salidroside under oxygen‒glucose deprivation (OGD) conditions and were either treated with recombinant MIF (rMIF) or transfected with Mif-siRNA. Subsequently, mitochondrial quality control and apoptosis were assessed. Results Salidroside enhanced mitochondrial quality control in MI model mice, mitigated apoptosis and improved cardiac dysfunction. Transmission electron microscopy indicated that there were fewer damaged mitochondria in the salidroside-treated mice compared with the control mice. MIF and downstream mitochondrial quality control pathways were activated in the mice treated with salidroside. Consistently, the cell experiments demonstrated that salidroside and rMIF alleviated apoptosis, improved impaired mitochondrial quality control in OGD-induced cells and activated MIF signaling in OGD-induced cells. However, these effects of salidroside were partially blocked by Mif-siRNA transfection. Conclusion Salidroside alleviated myocardial apoptosis and ameliorated cardiac dysfunction in MI model mice through the MIF pathway and downstream mitochondrial quality control.